Endocrine disruption of adipose physiology: Screening in SGBS cells - Kucera, Jan; Chalupova, Zuzana; Wabitsch, Martin; Bienertova-Vasku, Julie (Journal of applied toxicology, 2024)
The increasing use of industrial chemicals has raised concerns regarding exposure to endocrine-disrupting chemicals (EDCs), which interfere with developmental, reproductive and metabolic processes. Of particular concern is their interaction with adipose tissue, a vital component of the endocrine system regulating metabolic and hormonal functions. The SGBS (Simpson Golabi Behmel Syndrome) cell line, a well-established human-relevant model for adipocyte research, closely mimics native adipocytes' properties. It responds to hormonal stimuli, undergoes adipogenesis and has been successfully used to study the impact of EDCs on adipose biology. In this study, we screened human exposure-relevant doses of various EDCs on the SGBS cell line to investigate their effects on viability, lipid accumulation and adipogenesis-related protein expression. Submicromolar doses were generally well tolerated; however, at higher doses, EDCs compromised cell viability, with cadmium chloride (CdCl2) showing the most pronounced effects. Intracellular lipid levels remained unaffected by EDCs, except for tributyltin (TBT), used as a positive control, which induced a significant increase. Analysis of adipogenesis-related protein expression revealed several effects, including downregulation of fatty acid-binding protein 4 (FABP4) by dibutyl phthalate, upregulation by CdCl2 and downregulation of perilipin 1 and FABP4 by perfluorooctanoic acid. Additionally, TBT induced dose-dependent upregulation of C/EBPα, perilipin 1 and FABP4 protein expression. These findings underscore the importance of employing appropriate models to study EDC-adipocyte interactions. Conclusions from this research could guide strategies to reduce the negative impacts of EDC exposure on adipose tissue.
Keywords: Adipocytes; Cell Line; Dose-Response Relationship, Drug; Fatty Acid-Binding Proteins; vztah mezi dávkou a účinkem léčiva; tukové buňky; adipogenesis; adipocyte; kapryláty; Simpson Golabi Behmel Syndrome cell line; fluorokarbony; endocrine disruptors; adipogeneze; endokrinní disruptory; Fluorocarbons; Lipid Metabolism; Endocrine Disruptors; Humans; Caprylates; trialkylcínové sloučeniny; metabolismus lipidů; viabilita buněk; Cell Survival; Adipose Tissue; buněčné linie; SGBS cells; proteiny vázající mastné kyseliny; tuková tkáň; Trialkyltin Compounds; Adipogenesis; lidé